RANCANG BANGUN OBSTACLE AVOIDANCE PADA DIFFERENTIAL STEERING MOBILE ROBOT - Wardana, Galih Kusuma; Widyantara, Helmy; Susanto, Pauladie (Journal of Control and Network Systems, 2014)
Abstract: Various ways can be done to get to a location with long lines or the lines were short. A system that can determine the best path that has a good navigation system as well as support for Â sensors detecting the presence of an obstacle so that a system is not crashing and to the location safely. This study focuses on the differential steering to avoid obstacles the mobile robot, which the system uses a mobile robot that can detect the presence of an obstacle around the robot and avoid it. The mobile robot system is the support system or sub-system which supports the navigation system. Datas Â from this study were taken from the articles from the internet and this study using the method of analysis of literature study of the theory in the book. Based on the datas taken from literature and articles, to design ranging from hardware and software, and manufacture of software and hardware, integrates all these systems into a mobile robot system and test the entire system. Modules that is used in this system include: Differential Drive Robot; Dagu Rover 5 4WD; Microcontroller Atmega 128; DT-AVR ATmega1280 CPU MODULE; Rotary Encoder; DC motors; Motor controllers; and Liquid Cristal Display (LCD). Software design of this system, among others, to detect obstacles and comparing the distance between the obstacle is detected by the robot and choose which direction the robot avoidance and path safer to avoid being in a collision. The results of this study are an obstacle avoidance system on the differential steering mobile robot managed to dodge the obstacle and reach the desired location without bumping into objects or obstructions are nearby.Keyword: mikrokontroller, obstacle avoidnce System, differential steering mobile robot.Â